A Welcome, A Warning, and A Wish: On Entering a Doctoral Program in Educational Leadership for Social Justice in the Year 2020. (March 2023) - Alexander, Bryant Keith
After the cancelation of the International Congress of Qualitative Inquiry (2020) due to the Coronavirus pandemic (COVID-19), the substantive content of my presentation for the plenary, "Higher Education in the Time of Trump: Resistance and Critique" came into confluence with my invitation to deliver the 2020 Keynote to the 17th Incoming Cohort of the doctorate program in Educational Leadership for Social Justice, School of Education, Loyola Marymount University. This presentation delivered via ZOOM on June 18, 2020, calls forth a broader confluence of our current political climate under the "leadership" of Donald J. Trump, COVID-19, and national social justice activism linked with the Black Lives Matter Movement. Truly we are living protest and recovery in repressive times with a connectivity between the three. This message is both particular and plural to the audience that it was originally presented, and now to a diverse readership in these repressive times.